Sustainable synthesis, reduction and applications of graphene obtained from renewable resources - Torres, F.G.; Troncoso, O.P.; Rodríguez Achata, L.; De-la-Torre, G.E. (Elsevier, 2021)
Graphene is a revolutionary material with outstanding electrical, mechanical, thermal, and structural properties. The synthesis of graphene and its derivatives generally requires expensive and poisonous reagents. However, contemporary research efforts are switching towards more sustainable routes. The present review focused on the synthesis, performance, and applications of graphene-derived nanomaterials synthesized from waste biomass and reduced by green alternatives. Graphitization of waste carbon precursors is the most used method to obtain high purity graphite alternatives. Other methods, such as CVD, hydrothermal, laser, and CAS, have been investigated. Graphene yielded from biomass precursors exhibits properties similar to those from conventional sources. Green reduction of graphene oxide is carried out mostly by plant extracts from fruits, leaves, and other parts, which contain a high concentration of phenolic compounds. The as-prepared bio-waste and green-reduced graphene alternatives were applied in wastewater treatment, electrochemical storage devices, and metal ion sensors. In some cases, graphene showed significantly better performance than previous carbon-based nanomaterials reported in the literature. Despite being in its early stages of development, green-synthesized graphene has demonstrated great potential. As the interest in the development of sustainable alternatives continues to grow, future graphene research is expected to aim for this new line of research.
Keywords: Graphene; Reduction (mathematics); Renewable energy; Renewable resource; Materials science; Nanotechnology; Biochemical engineering; Environmental science; Natural resource economics; Chemistry; Engineering; Economics; Mathematics; Electrical engineering; https://purl.org/pe-repo/ocde/ford#2.03.00